ELECTRON MICROSCOPIC AUTORADIOGRAPHY OF GERMINAL CENTER CELLS IN MOUSE SPLEEN - Swartzendruber, D. C. (The Rockefeller University Press, 1965)
The fine structure of tritiated thymidine-labeled cells in antigen-stimulated mouse spleen germinal centers is described. In studies on the ultrastructural level, two labeled cell types found in germinal centers are observed. Large lymphocytes are characterized by their very numerous free ribosomes, a paucity of endoplasmic reticulum, relatively few mitochondria, and a poorly developed Golgi region. The nuclei are large and vesicular, and large nucleoli are present. A second labeled cell type appears to contain more mitochondria and has a higher development of the Golgi area. The nucleus contains large, numerous blocks of chromatin, indicative of a more differentiated cell type. Reticular cells, both phagocytic and non-phagocytic, were not observed to be labeled in the germinal centers.